Studying the Mechanism of Plasmopara viticola RxLR Effectors on Suppressing Plant Immunity - Xiang, Jiang; Li, Xinlong; Wu, Jiao; Yin, Ling; Zhang, Yali; Lu, Jiang (Frontiers in Microbiology, 2016)
The RxLR effector family, produced by oomycete pathogens, may manipulate host physiological and biochemical events inside host cells. A group of putative RxLR effectors from Plasmopara viticola have been recently identified by RNA-Seq analysis in our lab. However, their roles in pathogenesis are poorly understood. In this study, we attempted to characterize 23 PvRxLR effector candidates identified from a P. viticola isolate ‘ZJ-1-1’. During host infection stages, expression patterns of the effector genes were varied and could be categorized into four different groups. By using transient expression assays in Nicotiana benthamiana, we found that 17 of these effector candidates fully suppressed programmed cell death elicited by a range of cell death-inducing proteins, including BAX, INF1, PsCRN63, PsojNIP, PvRxLR16 and R3a/Avr3a. We also discovered that all these PvRxLRs could target the plant cell nucleus, except for PvRxLR55 that localized to the membrane. Furthermore, we identiﬁed a single effector, PvRxLR28, that showed the highest expression level at 6 hpi. Functional analysis revealed that PvRxLR28 could significantly enhance susceptibilities of grapevine and tobacco to pathogens. These results suggest that most P. viticola effectors tested in this study may act as broad suppressors of cell death to manipulate immunity in plant.